Implementation of Affective Domain Assessment in Islamic Religious Education Learning at SDN Rampal Celaket 2 Malang - Hazyimara, Karunia; Nurasia, Nurasia; Itsnainy, Siti Khairani (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Affective domain assessments that assess the emotional, motivational, attitude, interest, and spirit of learners have the same urgency as cognitive and psychomotor domains. The three domains that are the learning objectives are important positions in learning. But in actualization, the psychomotor and affective domains are often ignored, because they are too complicated and long in time. While the cognitive realm that emphasizes knowledge gets the maximum portion. This is an interesting thing to discuss with the aim of analyzing the assessment of the affective domain in PAI learning at SDN Rampal Celaket 2 Malang along with its supporting and inhibiting factors. Researchers will conduct research with a qualitative-descriptive approach to examine the assessment of affective domains in PAI learning at SDN Rampal Celaket 2 Malang. The data that has been obtained and collected will be analyzed using Milles and Huberman data analysis which includes data reduction, data presentation and conclusions from the data that has been analyzed. According to research that has been conducted, it shows that the assessment of the affective realm at SDN Rampal Celaket 2 Malang is carried out in several stages, there are planning, implementation, and evaluation. In planning, teachers make tables containing statements and assessment scales to be used in their implementation. The implementation is carried out through observation of students and conducting interviews with other teachers. While in the evaluation, the teacher analyzes the non-achievement of students at the assessment threshold. Students who are below the threshold will receive treatment to improve their affective learning outcomes.